Hydrogeological functioning of a karst aquifer deduced from hydrochemical components and natural organic tracers present in spring waters. The case of Yedra Spring (Southern Spain) - Mudarra, Matías; Andreo, Bartolomé (Acta Carsologica, 2010)
<span style="color: black; line-height: 115%; font-family: "Calibri","sans-serif"; font-size: 9pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: "Minion Pro"; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">The major chemical parameters, TOC and natural fluorescence of Yedra spring, Malaga province, southern Spain were monitored from April 2008 to March2009. The electrical conductivity and the concentrations of most major ions decreased following recharge periods. The TOC and NO<span style="line-height: 115%; font-family: "Calibri","sans-serif"; font-size: 6pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: "Minion Pro"; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">3<span style="line-height: 115%; font-family: "Calibri","sans-serif"; font-size: 6pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: "Minion Pro"; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">–<span style="color: black; line-height: 115%; font-family: "Calibri","sans-serif"; font-size: 9pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: "Minion Pro"; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">, representing tracers from the soil that infiltrate throughthe unsaturated zone, were found to vary inversely withthe Mg<span style="line-height: 115%; font-family: "Calibri","sans-serif"; font-size: 6pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: "Minion Pro"; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">2+ <span style="color: black; line-height: 115%; font-family: "Calibri","sans-serif"; font-size: 9pt; mso-ascii-theme-font: minor-latin; mso-fareast-font-family: Calibri; mso-fareast-theme-font: minor-latin; mso-hansi-theme-font: minor-latin; mso-bidi-font-family: "Minion Pro"; mso-ansi-language: SL; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;">content, whichis a natural indicator of groundwater residence time. Furthermore, a strong, direct relation was found between TOC and the natural fluorescence associated withhumic and fulvic acids. Bothparameters respond similarly to rainfall events, exhibiting significant increases during recharge followed by reductions during recession. This relation means that TOC mainly originates from organic acids. The results document rapid infiltration processes witha lag of less than one day following rainfall, whichis typical of a karst aquifer withconduit flow, rapid drainage and limited natural regulation. The combined use of conventional hydrochemical parameters and natural organic tracers facilitates aquifer characterization and validates the vulnerability to contamination.